Burst capacity analysis of pipeline with multiple longitudinally aligned interacting corrosion defects subjected to internal pressure and axial compressive stress - Arumugam, T. (Springer Nature, 2020)
This paper describes the application of finite element method (FEM) to predict the failure pressure of corrosion-affected pipes, specifically for pipes with multiple internal (2 and 3 defects) longitudinally aligned interacting corrosion defects subjected to internal pressure and axial compressive stress. The FEM was verified against results of full-scale burst tests. The developed FEM incorporated material nonlinearity, which allows for large strains and displacements. Furthermore, true ultimate tensile strength (UTS) instead of the typical engineering UTS was employed to determine the point of failure. The pipes used in the finite element analysis (FEA) were modeled based on API 5L X52 with a length of 2000Â mm, a nominal outer diameter of 300Â mm, and a nominal wall thickness of 10Â mm. The results obtained from the FEA were presented in a graph form and then used to determine the failure pressure trendlines of multiple longitudinally aligned interacting corrosion defects for varying defect depths and spacing between defects. In addition, the failure pressure trendlines of multiple longitudinally aligned interacting defects were compared to determine their differences. As expected, 3 longitudinally aligned interacting defects showed lower failure pressure compared to 2 longitudinally aligned interacting defects. Â© 2020, Springer Nature Switzerland AG.